Molecular Characterization And Validation Of Micro Satellite Markers Linked With Grain Yield Components For Drought Tolerance In Wheat (Triticum Aestivum L.) (Applied Biological Research, 2015)
The present study was aimed to enhance breeding efficiency, parental  genetic distance and conferring drought tolerance in wheat. Eight,  diverse wheat genotypes were selected as parents, crosses attempted in a  diallel fashion (excluding reciprocals) and 28 F1s developed. One  hundred six F2 plants taken from cross between DBW 17 (drought  susceptible) and WH 1080 (drought tolerant) were evaluated. Grain  yield showed significant positive correlation with effective tillers plant-1,  grains spike-1, biomass plant-1 and harvest index and significant negative  correlation with days to heading and days to anthesis in F2 populations  indicating the feasibility of improving grain yield. A total of 42 amplicons  were detected in 106 F2 plants and the number of amplicons locus-1 ranged from 1-3 with an average of 2.10 amplicons locus-1. In cross DBW  17 × WH 1080 dendrogram was constructed and genotypes got clustered  into eight major groups at the similarity coefficient value of 0.56. Cluster  Iincluded droughtsusceptible parent DBW17 and cluster II had tolerant  drought parent WH 1080. The markers showed 3.7 and 18.0%  phenotypic variation in drought condition traits viz., effective tillers  plant-1 and coleoptile length, respectively. Marker Xgwm573 was found associated with days to heading and days to anthesis and Xgwm369 with  1000-grain weight, coleoptile length and chlorophyll content.
Keywords: Drought tolerance; microsatellites (SSRs); single marker analysis; variability; wheat